Anapedia – An Open Web-based Encyclopedia for Indonesian Children - Nur Hayatin; Rizky Ade Mahendra; Dwi Arif Al-mubarok; Ahmad Dhana Renomi; Elbert Setiadharma; Adhi Bagus Setiawan; Tri Fidriyan Arya; Farid Dadhee; Fadil Ramadhan; Sandy Young; Ahmad Al Ghivani (Universitas Airlangga, 2019)
Background: The limited number of web and child applications becomes a challenge especially providing web or education app that can be a source of information referral to help the school task, especially for the needs of children in Indonesia.Objective: This study answers the challenge by designing a special encyclopedia for children called Anapedia, an open web-based encyclopedia for children.Methods: Anapedia designed for the quality of content for education and design for entertainment that is suitable for children's needs by considering the children cognitive abilities.Results: The features are full-color, simple layout, large font sizes, and simple language with illustrated drawing to make it easier. For maintain the quality of the articles, this app involves the educator as a contributor who have better understand the characteristic and need of school-level children. This also provided a search feature based on keywords using information retrieval system with spell checker.Conclusion: The results of testing result with Black Box Method, it can be concluded that the entire system being tested has been functioning properly in accordance with expectations.